Computerized budgeting model for University of the Philippines Food Service Diliman campus - Phichitr Laohasongkram
The primary purpose of this thesis is to develop a computerized budgeting model for the University of the Philippines Food Service, Diliman Campus. This model is built not only to provide a basic framework for analysis of the interrelated functions of the University of the Philippines Food Service but primarily to generate information which management can use for making decision and as a guideline for developing alternative courses of action when there are changes in the environment of the system. The model is not maximizing in the economist's sense, but is "satisficing" in the Simon sense. It intends only to achieve a satisfactory subsidy target by experimenting with sales, costs and prices values. The model can be used to determine the effects of various assumptions. Another purpose of this thesis is to stimulate the use of financial models in the planning of the U.F.S. The model developed in this study is a first attempt in this direction. The use of this model can indicate areas of improvement and direction for further development.